2020
DOI: 10.1021/acs.jafc.0c05906
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Iso-Esculeoside B from Tomato Fruits and LC–MS/MS-Based Food Screening for Major Dietary Steroidal Alkaloids Focused on Esculeosides

Abstract: Plants from the Solanaceae family are known to be sources of several nutritionally relevant steroidal glycoalkaloids (SGAs). With the aim of quantitatively investigating the occurrence of the main SGA from tomatoes, eggplants, and potatoes in various food samples and evaluating their relevance in the human diet, a rapid single-step extraction liquid chromatography–tandem mass spectrometry method was developed. Over the course of isolating several commercially unavailable SGAs from tomato products to use them a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
(80 reference statements)
3
8
0
Order By: Relevance
“…This finding agrees with the current model that early pathway intermediates are converted to late pathway during ripening (Yamanaka et al, 2009;Itkin et al, 2011). Average values for individual alkaloids ranged between 0.1 and 7.6 mg/100 g fresh weight (Table S1,2), demonstrating tomato steroidal alkaloids exist in concentrations higher than previously thought (Friedman, 2002;Caprioli et al, 2014;Baldina et al, 2016), and consistent with more recent reports (Steinert et al, 2020). Prominent tomato phytochemical classes like carotenoids are often found between 0.09 to 9.93 mg/100 g fresh weight (Dzakovich et al, 2019), suggesting steroidal alkaloids can be found in comparable concentrations.…”
Section: Association Determined By Gwas Are Validated In a Biparentalsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding agrees with the current model that early pathway intermediates are converted to late pathway during ripening (Yamanaka et al, 2009;Itkin et al, 2011). Average values for individual alkaloids ranged between 0.1 and 7.6 mg/100 g fresh weight (Table S1,2), demonstrating tomato steroidal alkaloids exist in concentrations higher than previously thought (Friedman, 2002;Caprioli et al, 2014;Baldina et al, 2016), and consistent with more recent reports (Steinert et al, 2020). Prominent tomato phytochemical classes like carotenoids are often found between 0.09 to 9.93 mg/100 g fresh weight (Dzakovich et al, 2019), suggesting steroidal alkaloids can be found in comparable concentrations.…”
Section: Association Determined By Gwas Are Validated In a Biparentalsupporting
confidence: 92%
“…In the case of hydroxytomatine, acetoxytomatine, dehydrolycoperoside F/G/dehydroesculeoside A, lycoperoside F/G/esculeoside A, and esculeoside B, multiple peaks are observed, confirming the presence of structural isomers (Manabe et al, 2013;Nohara et al, 2015;Hövelmann et al, 2019;Steinert et al, 2020). For example, lycoperoside F, G, and esculeoside A (C58H95NO29, monoisotopic mass = 1269.5990 Da), are isobaric (Yahara et al, 2004) and exhibit similar fragmentation patterns since their molecular differences are limited to subtle changes in stereochemistry on the F ring (Dzakovich et al, 2020).…”
Section: Land-races and Wild Tomato Species Exhibit Steroidal Alkaloid Chemical Diversitymentioning
confidence: 71%
“…Average values for individual alkaloids ranged between 0.1 and 7.6 mg 100 g −1 fresh wt. (Supplemental Tables S1 andS2), demonstrating tomato steroidal alkaloids exist in concentrations higher than previously thought (Baldina et al, 2016;Caprioli et al, 2014;Friedman, 2002) and consistent with more recent reports (Steinert et al, 2020). Prominent tomato phytochemical classes like carotenoids are often found between 0.09 and 9.93 mg 100 g −1 fresh wt.…”
Section: Diversity For Steroidal Alkaloids Is Greatest In Landrace An...supporting
confidence: 89%
“…In the case of hydroxytomatine, acetoxytomatine, dehydrolycoperoside F/G/dehydroesculeoside A, lycoperoside F/G/esculeoside A, and esculeoside B, multiple peaks are observed, confirming the presence of structural isomers (Hövelmann et al., 2020a; Manabe et al., 2013; Nohara et al., 2015; Steinert et al., 2020). For example, lycoperoside F, G, and esculeoside A (C 58 H 95 NO 29 , monoisotopic mass = 1269.5990 Da) are isobaric (Yahara et al., 2004) and exhibit similar fragmentation patterns since their molecular differences are limited to subtle changes in stereochemistry on the F ring (Dzakovich et al., 2020).…”
Section: Resultsmentioning
confidence: 85%
“…Fruit category classification (FCC) may benefit factory automatic transportation and fruit‐packing (Tian et al, 2020), price and consumer desirability prediction (Kirk et al, 2019), and dietary intake (Steinert et al, 2020). FCC still remains a challenge because it is tough to specify an accurate definition of a type of fruit.…”
Section: Introductionmentioning
confidence: 99%